Job search requirements for older unemployed: Transitions to employment, early retirement and disability benefits - Hans Bloemen; Stefan Hochguertel; Marloes Lammers (Institute for the Study of Labor (IZA), 2011)
In this paper, we use a recent policy change in the Netherlands to study how changes in search requirements for the older unemployed affect their transition rates to employment, early retirement and sickness/disability benefits. The reform, becoming effective on January 1st 2004, required the elderly to formally report their job search efforts to the employment office in order to avoid a (temporary) cut in benefits. Before the new law was passed, unemployed were allowed to stop all search activity at the moment they turned 57.5. Estimating various duration models using difference-in-difference and regression discontinuity approaches, we find that for several groups of individuals that were affected by the policy change, the stricter search requirements did significantly increase their entry rate into employment. However, we also find evidence of a higher outflow to sickness/disability insurance schemes, a presumably unwanted side-effect of the policy change.
urn:nbn:de:101:1-201104113152
Keywords: C31; J26; J64; J68; 330; duration analysis; policy evaluation; search effort; substitution; Arbeitslosigkeit; Arbeitsuche; Ältere Arbeitskräfte; Beschäftigungseffekt; Niederlande